2022
DOI: 10.3390/s22031010
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Spatiotemporal Attention Network for Remote Heart Rate Variability Analysis

Abstract: Studies have shown that ordinary color cameras can detect the subtle color changes of the skin caused by the heartbeat cycle. Therefore, cameras can be used to remotely monitor the pulse in a non-contact manner. The technology for non-contact physiological measurement in this way is called remote photoplethysmography (rPPG). Heart rate variability (HRV) analysis, as a very important physiological feature, requires us to be able to accurately recover the peak time locations of the rPPG signal. This paper propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The results showed that, at this stage, none of the participants demonstrated any signs of stress. For the random forest model trained on the SWELL dataset, an impressive detection rate was observed, with all 5 participants showing signs of stress As shown in Table 11, our proposed method performed better than traditional CHROM [18], FaceRPPG [19] methods, and deep learning-based PulseGAN [18], Phys-Net, [19], rPPGGAN [37], ESA-rPPGNet [19] methods. In the custom dataset, our proposed system showed an accuracy of 95% for HR and 82% for overall HRV features Table 12.…”
Section: Mean_rr Sdrr Rmssd Sdsd Pnn50 Pnn25 Sd1 Sd2 Vlf Lf Hf Lf/hfmentioning
confidence: 83%
See 2 more Smart Citations
“…The results showed that, at this stage, none of the participants demonstrated any signs of stress. For the random forest model trained on the SWELL dataset, an impressive detection rate was observed, with all 5 participants showing signs of stress As shown in Table 11, our proposed method performed better than traditional CHROM [18], FaceRPPG [19] methods, and deep learning-based PulseGAN [18], Phys-Net, [19], rPPGGAN [37], ESA-rPPGNet [19] methods. In the custom dataset, our proposed system showed an accuracy of 95% for HR and 82% for overall HRV features Table 12.…”
Section: Mean_rr Sdrr Rmssd Sdsd Pnn50 Pnn25 Sd1 Sd2 Vlf Lf Hf Lf/hfmentioning
confidence: 83%
“…The results of these experiments are presented in Figures 7 and 8 and Table 11. As shown in Table 11, our proposed method performed better than traditional CHROM [18], FaceRPPG [19] methods, and deep learning-based PulseGAN [18], PhysNet, [19], rPPGGAN [37], ESA-rPPGNet [19] methods. In the custom dataset, our proposed system showed an accuracy of 95% for HR and 82% for overall HRV features Table 12.…”
Section: Datasetmentioning
confidence: 89%
See 1 more Smart Citation
“…A novel multitask temporal shift convolutional attention network (MTTS_CAN) was used to measure HR and Respiration rate (Resp), which leveraged Temporal Shift Models (Lin et al 2018) (TSMs) instead of 3D-CNN to perform efficient temporal modeling and uses the self-attention module (Liu et al 2020). An efficient spatiotemporal attention network (ESA-rPPGNet) was proposed to recover high-quality BVP signal for HRV, which adopted 3D depth-wise separable convolution and a structure based on mobile net v3 to greatly reduce the time complexity of the network (Kuang et al 2022). However, both Liu et al (2020) and Kuang et al (2022) only consider extracting spatiotemporal features from video and do not pay attention to recover the BVP signal shapes.…”
Section: Introductionmentioning
confidence: 99%
“…An efficient spatiotemporal attention network (ESA-rPPGNet) was proposed to recover high-quality BVP signal for HRV, which adopted 3D depth-wise separable convolution and a structure based on mobile net v3 to greatly reduce the time complexity of the network (Kuang et al 2022). However, both Liu et al (2020) and Kuang et al (2022) only consider extracting spatiotemporal features from video and do not pay attention to recover the BVP signal shapes. TS_CAN model is no difference from MTTS_CAN except that MTTS_CAN can predict BVP signals and Resp signal at the same time but TS_CAN can only predict BVP signal.…”
Section: Introductionmentioning
confidence: 99%